The Effectiveness of Problem Based Learning Model on Understanding Concepts and Science Process Skills As Implementation Independent Curriculum - Andriono Manalu; Aprido Simamora; Ika Damayanti Purba; Novita Sinaga (Jurnal Ilmu Sosial dan Humaniora, 2026)
Learning outcomes in the science subjects emphasize the competencies of conceptual understanding and process skills. Learning outcomes in science, especially physics, are essentially related to how to systematically find out about nature, so that science is not only the mastery of a body of knowledge in the form of facts, concepts, or principles but also a process of discovery through investigation or experimentation. Investigation or experimentation can train students to acquire scientific process skills. In addition to developing scientific process skills, physics learning is expected to encourage students to become active learners and think critically in analyzing and applying concepts to solve problems in everyday life. Related to the above problem, there is a need for a model that orients learning to real problems that can create student involvement in the teaching and learning process to cultivate, develop scientific process skills and foster conceptual understanding in solving students' problems. Getting used to scientific work is expected to foster habits of thinking and acting that reflect students' mastery of scientific knowledge, skills, and attitudes, so that the learning model will automatically result in increased scientific knowledge, skills, and attitudes of students as a result of learning. The characteristics of the model above are in the Problem-Based Learning Model. One characteristic of problem-based learning is that the problems presented are expected to have no single answer or single solution. This provides a very broad opportunity for students to explore their potential. Students have the freedom according to their nature in different or differentiated ways. Differentiated learning is creating a diverse class by providing opportunities to acquire content, process an idea and improve the results of each student, so that students can learn more effectively. By using the Problem Based Learning model integrated with differentiated learning, it is hoped that it can facilitate students in expressing their freedom in learning. The output to be achieved is publication in a SINTA-accredited journal, which can be cited by other researchers